Enabling a generation of social entrepreneurs: A study to establish if the practice of social entrepreneurship offers inclusive self-employment opportunities for disenfranchised South African youth - Carpenter, Janine (Graduate School of Business, 2019)
This study is concerned with contributing to solutions that address the problems of youth unemployment, inequality and poverty in South Africa, specifically among those youth who are being marginalised from participating equally in mainstream economic activities. It argues that financial and digital exclusion, as well as poor access to a quality education, are factors which are currently limiting these youths' economic potential and perpetuating a cycle of unemployment, inequality and poverty in South Africa. The literature and theory of social entrepreneurship presents a strong case to address unemployment, inequality and poverty, as well as to stimulate economic growth by creating new business and self-employment opportunities for the youth. This qualitative grounded theory study evaluates the theory of social entrepreneurship in practice, by comparing the theory to the lived realities of some disenfranchised youths in Cape Town. The study also provides an analysis of the systems of privilege and the dual economy that exist in South Africa. Through feedback received during interviews with a representative sample of the target group, the study offers new insights into the challenges faced when young people are seeking employment or want to start a business in the South African economy. Youth social entrepreneurship development and start-up incubation programmes arguably perform a critical function in facilitating inclusive economic participation among the youth. Developing new insights, concepts and recommendations to maximise these programmes' social impact is a critical function of this study, which ultimately hopes to contribute to the creation of more inclusive entrepreneurial opportunities for disadvantaged South African youth.